Tenganan Pegringsingan Bali In Ethnography - Wirawan, I Komang Arba (Institut Seni Indonesia Denpasar, 2019)
The purpose of this study is to create photos that visualize the activities of the Tenganan Pegringsingan community based on Tri Hita Karana’s cause of happiness to achieve balance and harmony. First, Parahyangan is a balanced relationship between humans and God, second, Pawongan a harmonious relationship between humans and humans, and thirdly Palemahan means a harmonious relationship between humans and the surrounding natural environment. This research and photography creation method was in the form of in-depth data exploration (depth observations) in the form of interviews and observations. Art and cultural activities and ceremonies in Pegringsingan Village were explored through in-depth research and presented with the concept of ethnophotography. Ethnography does not see a photograph of the work alone, but it is an ethnographic method of viewing society from an anthropological perspective. The anthropological world of photography emphasizes the extraordinary side of conventional things. The harmony of life-based on Tri Hita Karana was reflected in the Tenganan Pegringsingan community as the subject matter of ethnographic creation. Ethnographic results and analysis in Tenganan Village were dissected with the aesthetic theory of photography. First, the aesthetic of photography created through the beauty of photographs based on an ideational and technical level. It was the ethnographic ideational level of upakara in Tenganan Pegringsingan Village. The technical level was related to technical concerning the equipment used for creation. The second theory of semiotic photography analyzed photographs based on the signs contained in the photo. The results of the ethnographic creation of the community in Tenganan Pegringsingan Village found a harmonious relationship between the community and nature, humans and God in the village. This relationship is the subject of representative ethnophotography. The results of ethnographic creation reflect harmonious relationships through the implemented ceremonies that reflect Tri Hita Karana.